The influence of internship determinants on hospitality undergraduates’ satisfaction level: A case of public universities in Malaysia / Syafinaz Ruslan … [et al.] - Ruslan, Syafinaz; Mohamad, Siti Fatimah; Juhari, Nurul Hanisah; Abdul Karim, Muhammad Shahrim (Universiti Teknologi Mara Selangor, 2019)
Being a university undergraduate no longer guarantees job placement. Previous literature has proven that the work experiences of an internship program make a significant impact on students' career choices as it provides students with realistic expectations of their future careers. Students who have undergone their internship program agree that internship satisfaction would have a strong influence on their career intentions. Although several studies emphasized on student internship experiences and career intention, there is a lack of empirical research that has been carried out on the relationship between internship determinants and internship satisfaction, particularly within the hospitality context. Therefore, this present study aims to examine the factors associated with internship satisfaction. There are three factors identified as the determinants of the internship satisfaction, namely job characteristics, organizational environment, and contextual factors. A quantitative research method involving 302 hospitality undergraduates from seven public universities that offer Bachelor in Hospitality and Food Service courses in Malaysia had been conducted. Findings from the three independent variables (job characteristics, organizational environment, and contextual factors) show that the organizational environment has the highest impact on internship satisfaction (beta = .480), followed by job characteristics (beta = .366), and contextual factors (beta = .113).